Desain Jaringan Fiber to The Home di Desa Butuh Kidul - Prastowo, Imana Yoga; Yulianto, Sri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study aims to design a Fiber to the Home (FTTH) network in Butuh Kidul Village, Tengaran District, Semarang Regency. In today's digital era, access to fast and stable internet is a fundamental need for communities. However, many rural areas in Indonesia, including Butuh Kidul Village, still lack adequate internet access. FTTH networks provide a solution by utilizing fiber optic cables that can transmit data at high speeds and with large bandwidth capacity. This research employs the Passive Optical Network (PON) method as the network architecture to enhance efficiency and scalability. The expected outcome is that the local community will benefit from improved internet access, supporting digital village programs and enhancing the quality of life and economic potential. This research is anticipated to serve as a reference for similar network developments in other rural areas.